2022
DOI: 10.3389/fphar.2022.815308
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Suppresses Paclitaxel Sensitivity by Regulating Akt-Mediated Phosphorylation of Bax in EGFR Wild-Type Non-Small Cell Lung Cancer Cells

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common and deadly cancers worldwide. Among NSCLC patients, almost half have wild-type epidermal growth factor receptor (EGFR WT). The primary therapeutic option for these EGFR WT NSCLC patients is chemotherapy, while NSCLC patients with EGFR mutations have more diverse therapeutic options, including EGFR tyrosine kinase inhibitors. Moreover, NSCLC patients with EGFR WT have worse chemotherapy response than EGFR mutant NSCLC patients. Thus, an urgent need ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Based on the Kyoto Encyclopedia of Genes and Genomes pathway analysis, we found that both DNA-PK and mTOR can promote the activation of Akt. Research has shown that Akt can disturb the BCL-2/Bax balance and inhibit cytochrome c release, suppressing apoptosis 57 , 58 . Interestingly, it has been suggested that the mitochondrial intrinsic pathway can also mediate cell pyroptosis via Bax-caspase-3-GSDME 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Kyoto Encyclopedia of Genes and Genomes pathway analysis, we found that both DNA-PK and mTOR can promote the activation of Akt. Research has shown that Akt can disturb the BCL-2/Bax balance and inhibit cytochrome c release, suppressing apoptosis 57 , 58 . Interestingly, it has been suggested that the mitochondrial intrinsic pathway can also mediate cell pyroptosis via Bax-caspase-3-GSDME 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in the surrounding environment of PTM sites could be a mechanism by which alternative splicing regulates protein function. For example, the apoptosis regulator BAX (encoded by gene BAX) induces apoptosis under stress conditions, while phosphorylation at 184S by RAC serine/threonine-protein kinase (AKT1) causes BAX to prevent apoptosis 44 . In α the BAX reference isoform (BAX ), 184S is located inside a helix and the side chain is oriented α toward the inside of the helix with a RSA of 1.18 Å 2 .…”
Section: Alternative Splicing Buries and Exposes Post Translational M...mentioning
confidence: 99%
“…2. Ligand dependency: (i) Auto-secretory ligand-dependent activation, in which tumor cells respond to increased expression of their HH ligands in a cell-autonomous manner (i.e., glioblastoma [ 201 ], neck squamous cell carcinoma [ 202 , 203 ], and lung [ 204 ], breast [ 205 , 206 ], ovarian [ 207 ], stomach [ 208 , 209 ], esophageal [ 210 ], pancreatic [ 211 ], and prostate cancers); (ii) Paracrine-ligand-dependent model, in which Hh ligands produced and released by tumor cells switch on HH signaling in the peripheral stroma, in turn facilitating tumor expansion and metastasis, and creating a positive feedback loop (i.e., prostate, ovarian [ 212 – 214 ], pancreatic [ 215 ] and colorectal cancers [ 216 , 217 ]); (iii) Reverse paracrine ligand-dependent signaling activation, indicates that Hh ligands are secreted from the stroma and received by tumor cells (i.e., multiple myeloma, lymphoma [ 218 ], and leukemia [ 219 , 220 ]). 3.…”
Section: Role In Cancer and Therapeutic Strategiesmentioning
confidence: 99%